IN VITRO ANTIMICROBIAL AND ANTI-INFLAMMATORY ACTIVITY OF METHANOL EXTRACT OF ERANTHEMUM CAPENSE - JOHN L, ANOOPA; N, KANNAPPAN; P, MANOJKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study was aimed to rationalize the scientific basis in traditional use of Eranthemum capense as an antibacterial, antifungal, and anti-inflammatory agent. Methods: Agar well diffusion method is widely used to evaluate the antimicrobial activity of the E. capense aerial part of methanolic and ethyl acetate plant extracts. The same amount (15–20 mL) of Mueller-Hinton agar was poured on glass Petri plates of same size and allowed to solidify. E. capense aerial part of methanolic and ethyl acetate extracts was evaluated in vitro for their anti-inflammatory activities using the bovine serum albumin protein denaturation assay. Results: The result of the study shows that methanolic exract (T3) of the plant, E. capense shows 16 mm zone of inhibition against Pseudomonas fluorescens, while the ethyl acetate extract of the same plant shows 14 mm zone of inhibition against P. fluorescens and E. coli. Hence the methanolic extract of T3 sample shows the antibacterial activity against gram negative bacteria, where as the ethyl acetate extract of T3 shows antibacterial activity against both gram positive and gram negative bacteria. The experimental report revealed that, the methanolic and ethyl acetate extract of the same plant produces zero percentage zone of inhibition against Aspergillus niger and Mucor, hence it does not show any antifungal activity. Conclusion: It is observed that the EA and methanolic extract of E. capense can be used in the treatment of inflammation due to the significant percentage of inhibition of protein denaturation as well as its prove the good antimicrobial agent.